33 Percutaneous coronary intervention in elderly patients – ten years' experience from a large non-surgical centre. (17th July 2020) - Abramik, Joanna; Dastidar, Amardeep; Kontogiannis, Nestoras; Patri, Gopendu; North, Victoria; Weight, Nicholas; Raina, Tushar; Kassimis, George
Abstract : Background: With an ageing population, the need for treating coronary artery disease in the elderly using percutaneous coronary intervention (PCI) is on the rise. Technical advances, better peri-procedural pharmacology and greater operator experience have led to improved outcomes after PCI. Octogenarians as a group, however, have been underrepresented in randomised clinical trials for coronary revascularisation. Observational studies therefore provide useful insights into the safety and efficacy of PCI in this patient population in a real-world setting. Aim: The aim of this study was to examine the trends in patient characteristics and clinical outcomes after PCI in octogenarians over a 10-year period in a large non-surgical PCI centre and to determine the predictors of mortality in this high risk patient cohort. Methods: A total of 782 consecutive octogenarians were identified from a prospectively collected database of all patients undergoing PCI at our centre over a 10-year period between 1st January 2007 and 31st December 2016. The analysis evaluated the characteristics of the cohort with respect to all-cause in- hospital and 1-year mortality, in-hospital Major Adverse Cardiovascular Events (MACE) rates, duration of hospital stay, complexity of coronary artery disease and major comorbidities. The cohort was stratified into three chronological tertiles to assess differences over time. A multivariate analysis was performed to determine predictors for mortality in this patient cohort. Results: The number of octogenarians undergoing PCI was found to have increased nearly ten-fold, from 19 in 2007 to 178 in 2016 (Figure 1 ). Despite this, there were no statistically significant differences in adverse clinical outcomes or peri-procedural patient characteristics (Table 1 ). A greater use of radial access for performing PCI was noted (p<0.0001), as well as increasing proportion of patients with multivessel disease (p=0.011). Increasing age, the presence of cardiogenic shock, severe left ventricular impairment, peripheral vascular disease, diabetes mellitus and low creatinine clearance were identified as independent predictors of mortality after PCI (Table 2 ). Conclusion: This study has shown that PCI in octogenarians is a safe and effective revascularisation option, which is increasingly being used in the real-world clinical practice. Further randomised clinical trial data is needed to enhance the evidence base for this challenging patient population. Conflict of Interest: None